City Power in the Age of Silicon Valley: Evaluating Municipal Regulatory Response to the Entry of Uber to the American City. (December 2022) - Wolf, Andrew
This article recasts the debate over the employment status of gig economy workers as a question about the power of municipal governance. Gig employers are challenging urban regulatory regimes through their disavowal of an employment relationship and their refusal to obtain taxi licenses. As the recent literature argues, there has been a resurgence of municipal power driven by a labor-antipoverty coalition. One might view the gig economy's independent contractor model as an attempt to circumvent this power. Analyzing the case of gig taxi companies like Uber, this article tracks the response of U.S. cities to a business model predicated on ignoring their regulations. Utilizing original data, this study investigates urban regulatory responses to Uber through descriptive statistics and multivariate modeling. The findings show that almost half of cities failed to regulate. Those that took action had historically greater levels of regulation and faced driver protests—a sign of a stronger labor-antipoverty coalition. Additional evidence indicates a learning effect in which cities became more likely to regulate over time. The article ends with a discussion of how workers and unions are responding to this challenge.